RESPON KPK TERHADAP REVISI UNDANG-UNDANG NO.30 TAHUN 2002 PADA TAHUN 2016 - Tari N R, Desak Nyoman; Erawan, I Ketut Putra; Bandiyah, Bandiyah (Jurnal Nawala Politika, 2020)
AB STRACT   This research purposed to explains how a country’s institution that independently facing of dynamics challenges corruption eradication, in this case Corruption Eradication Commssion (KPK). This research is using a state auxiliary institution theory by John Ackerman and social movement theory by Charles Tilly. This research is using descriptive qualitative methods. Data analyst techniques that uses in this research is analytical descriptive technique. The result of this research found that KPK in responding the plan of law of 30 year of 2002 revision with three form, those are: first, KPK as a institution officially denies KPK Law’s revision. Second, KPK internally responding the plan of KPK’s Law revision with the elements of supporting institution as translated into the way it works by authority, structure, actor, and networks. Third, KPK externally doing a response by a social movement that translated the element of organizating, the threat/opportunity and strategy of mobilization. Keywords: KPK, The Revision of KPK Law, Independently Country’s Institution, Social Movement